Роль жінки у розвитку науки - Качанов, С. А.; Кириченко, В. В. (ХНУРЕ, 2019)
This work is devoted to the problem of unjustified understatement of woman's role in the development of science. We have demonstrated great women's achievements in different branches of science. Marie Sklodowska Curie, Hedy Lamarr, Ada Lovelace, Grace Hopper, Mary Aiming are just a little part of the female scientists which are mentioned in our article and who really have made a scientific revolution in various areas of our lives. All of them can be a brilliant example of the fact that women are not inferior to men in the outstanding discoveries of mankind.